Adaptive AI Scaffolding within Gamified Reading Missions: Effects on Grade 10 Students Reading Comprehension in South Sulawesi - Firman Saleh; Hastuti Hamka; Selma Hachicha (PT. Sinergi Bersahaja Sejahtera, 2026)
Background. Reading comprehension remains a critical challenge in secondary education, while conventional instruction often provides limited opportunities for adaptive feedback and sustained student engagement. Purpose. This study examined the effectiveness of an AI assisted gamified learning strategy in improving the reading comprehension of Grade 10 students at SMA Negeri 4 Sidrap, South Sulawesi, Indonesia. Method. A quantitative quasi experimental method with a nonequivalent pretest posttest control group design was employed. The participants were 54 students divided into an experimental group (n = 29) and a control group (n = 25). Reading comprehension was measured using a 30 item test, and the data were analyzed using descriptive statistics and ANCOVA.was then processed using descriptive statistics in the form of percentages. Novelty. The study integrates AI generated adaptive scaffolding with structured gamification elements, including reading missions, progress indicators, achievement badges, and immediate feedback, within a unified reading instruction design. Results. The experimental group achieved a higher adjusted posttest mean than the control group (82.03 vs. 73.97). ANCOVA revealed a significant instructional effect, F(1, 51) = 15.00, p < .001, partial ?² = .227. Conclusion. AI assisted gamified learning effectively improved students’ reading comprehension and offers a promising adaptive approach for secondary school literacy instruction.